(untitled) (Research, Society and Development, 2020)
Cancer is the general name given to a set of more than 100 diseases, which have in common in the disordered growth of cells, which tend to invade neighboring tissues and organs. This pathology stands out for its high incidence and mortality rates. It is estimated that in the world in 2020, there will be approximately 15 million new cases. Its objectives are to understand the role of nurses in assisting palliative cancer patients. To analyze the role of nurses in front of SAE in the care of palliative cancer patients pointed out in scientific productions. This is a study of bibliographic review, of a descriptive nature and with a qualitative approach. Searches were carried out in the database of the Virtual Health Library (VHL), between June and November 2019. Four articles were analyzed, resulting in the formation of two categories: Care actions for cancer patients and influencing factors for the practice of care. The nursing team is of paramount importance to the patient in palliative care and also serves as support for the family, giving all necessary support and safety to the terminally ill patient, contributing to the patient’s comfort. The use of the nursing diagnosis brings benefits both to the patient and to the performance of the nursing activities themselves, as they guide through the nursing process, as to the individual needs of each patient. It is concluded that nursing is of paramount importance in assisting terminal cancer patients. SAE is the instrument used to systematize nursing care, and the nurse is primarily responsible for its applicability.